2019
DOI: 10.3389/fphar.2019.00029
|View full text |Cite
|
Sign up to set email alerts
|

The Ethanolic Extract of Caesalpinia sappan Heartwood Inhibits Cerebral Ischemia/Reperfusion Injury in a Rat Model Through a Multi-Targeted Pharmacological Mechanism

Abstract: Background: Caesalpinia sappan L. (C. sappan) is a traditional Chinese medicinal plant. The dried heartwood of C. sappan (also known as Sappan wood) has been widely used for the folkloric medical treatment of ischemic cerebral stroke in China. However, the detailed underlying pharmacological mechanism still remains largely unexplored.Methods: In this study, a middle cerebral artery occlusion (MCAO) rat model was employed to elucidate the mechanism of the anti-cerebral ischemic effects of C. sappan ethanolic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…The dried heartwood of Caesalpinia sappan L. is a traditional herb that could be used to accelerate blood circulation and remove blood stasis [11]. Recent studies have reported that the ethanolic extract of Caesalpinia sappan L. heartwood could protect HEI-OC1 cells against tert-butylhydroperoxide (t-BHP)-induced oxidative injury [12] and prevent cerebral ischemia reperfusion injury in a rat model [13]. SA is an active constituent isolated from Caesalpinia sappan L. heartwood and exhibits antioxidant, anti-inflammatory and anti-apoptotic activities.…”
Section: Discussionmentioning
confidence: 99%
“…The dried heartwood of Caesalpinia sappan L. is a traditional herb that could be used to accelerate blood circulation and remove blood stasis [11]. Recent studies have reported that the ethanolic extract of Caesalpinia sappan L. heartwood could protect HEI-OC1 cells against tert-butylhydroperoxide (t-BHP)-induced oxidative injury [12] and prevent cerebral ischemia reperfusion injury in a rat model [13]. SA is an active constituent isolated from Caesalpinia sappan L. heartwood and exhibits antioxidant, anti-inflammatory and anti-apoptotic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, medicinal plants have been proven their value as therapeutic sources for neurological disorders, including cerebral ischemia (ischemic stroke) [ 34 , 35 , 36 ]. In our current study, we evaluated the neuroprotective effects of pretreated PYC originating from the maritime pine bark in the CA1 area of gerbil hippocampus following TFI using histochemistry with CV, immunohistochemistry with NeuN, and histofluorescence with F-J B.…”
Section: Discussionmentioning
confidence: 99%
“…22 Notably, the ethanolic extract of Caesalpinia sappan L. heartwood has been reported to protect the brain against ischemia reperfusion injury in a middle cerebral artery occlusion (MCAO) rat model. 23 However, it is not clear exactly which ingredient plays an anti-ischemia role. These results suggested that SA is a major ingredient of Caesalpinia sappan L. that accounts for the anti-ischemia effect.…”
Section: Discussionmentioning
confidence: 99%